A Case Study Of Power Saving Initiatives In A Telecommunication Company - Dali, Daliza (2009)
The aim of this study is to provide the initiatives done by Telecommunication Company X in studying and implementing the power saving as part of operational expenditure reduction. The initiatives are concentrated to the power savings at the access part covering energy optimization. The alternative solutions available are reduction of energy consumption by increase of air conditioner temperature and energy efficiency equipments usage.